Criminal minds. The second season [videorecording (DVD)] - Patinkin, Mandy; Gibson, Thomas, 1962-; Glaudini, Lola, 1972-; Moore, Shemar, 1970-; Gubler, Matthew Gray, 1980-; Cook, A. J., 1978-; Vangsness, Kirsten, 1972-; Brewster, Paget, 1969- (CBS DVD : Paramount Home Entertainment, 2007)
Jason Gideon is the head of the FBI's Behavioral Analysis Unit (BAU) and mentor to an elite team of profilers, including family man Aaron Hotchner, sex-crimes expert Elle Greenaway, hunky Derek Morgan, genius-geek Dr. Spencer Reid, department liaison "JJ" Jareau, and computer whiz Penelope Garcia. Joining them this season is Emily Prentiss who quickly learns there's nothing these agents would rather do than profile murderers and put them away